Rádio UEL FM: recomendações para a organização de conteúdos temáticos - Paiva, Andréia Del Conte de (2018)
At first, radio broadcasting was used for military proposes, only in the end of the First Great War it earned repercussion in the society. In Brazil, it was idealized by Roquette Pinto e Henry Morize, who intent to create an educational and cultural radio. In the contemporary world, radio stations embraced an hypertextual context and count on various knowledge field associates to support this process. According to this context is worth to reminding that the web provides, among other aspects, an impressive amount of information which without the adequate organization, invalidate its identification, access and use. As consequence, this study has emphasized audible documents and presents as common thread the following questions: how audible documents are organized on the web environment of Radio UEL FM (aiming its fast and complete retrieval)? To guide the search for answers, it was composed a general objective, which proposes recommendations to organize information, namely, the thematic content in University Radio of State University of Londrina website. The methodology is focused on a descriptive exploratory study of quantitative approach which uses case study. Data collection was made through documental analyses, semi-structured interview and PVI. Data triangulation took place to grant reliability to results. In outline, it was found that regardless the respondents worry about the audible documents organization on the website, no considerable procedure was performed for its organization. The associates perception on repercussion and access of documents is rudimentary as they understand that it is enough knowing where the document is saved, not taking into consideration its content, which makes the search process exhausting and most of the times unsuccessful. In this regard, it is clear the relevance of the involvement of Information Science professionals, who by means of praised proceedings of this Field may contribute to the website organization and available documents, providing quality in access and information retrieval.